2004
DOI: 10.1017/s0021859604004319
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of new varieties to cereal yields in Finland between 1973 and 2003

Abstract: On the basis of Finnish statutory variety trial data, the contribution of new varieties to cereal yields has been investigated. Such data have been collected since 1973. The data used contained the results of 2037 field trials testing 224 new barley cultivars, 163 new oat cultivars, 154 new spring wheat cultivars, 48 new winter wheat cultivars and 52 new winter rye cultivars. The data indicated a continuous increase in the annual yield of all the cereal species. The increase could be attributed in part to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
3
9
0
1
Order By: Relevance
“…This was broadly similar to the annual increases reported by other studies such as 0.38 % by Humphreys (1999), 0.4-0.5 % by Easton et al (2002) and 0.4-0.6 % by Wilkins and Humphreys (2003). These rates of increase are significantly lower than in maize (2.6 %/year; Tollenaar 1989) and typically for cereals (1.0-1.5 %/year; Peltonen-Sainio and Karjalainen 1991;Silvey 1986;Ö fversten et al 2004;Caldenrini et al 1995). As reported widely and by Wilkins and Humphreys (2003) this is because grain yield improvements were achieved by repartitioning biomass from the shoot into the grain whereas grass yield improvements require total shoot biomass increases.…”
Section: Discussionsupporting
confidence: 87%
“…This was broadly similar to the annual increases reported by other studies such as 0.38 % by Humphreys (1999), 0.4-0.5 % by Easton et al (2002) and 0.4-0.6 % by Wilkins and Humphreys (2003). These rates of increase are significantly lower than in maize (2.6 %/year; Tollenaar 1989) and typically for cereals (1.0-1.5 %/year; Peltonen-Sainio and Karjalainen 1991;Silvey 1986;Ö fversten et al 2004;Caldenrini et al 1995). As reported widely and by Wilkins and Humphreys (2003) this is because grain yield improvements were achieved by repartitioning biomass from the shoot into the grain whereas grass yield improvements require total shoot biomass increases.…”
Section: Discussionsupporting
confidence: 87%
“…015 t/ha per year). Calderini &Slafer (1998) andÖ fversten et al (2004) analysed yield trends in long-term yield datasets for cereals but neither identified explicitly any trend due to changes in the climate. The difference between sugarbeet and wheat in response to climate changes is probably due to the different processes of yield formation.…”
Section: Discussionmentioning
confidence: 99%
“…If Sirius is used in the mode that takes account of changes in CO 2 concentration, then the simulated increase in grain yield over the whole period was 0·43 t/ha (or 0·015 t/ha per year). Calderini & Slafer (1998) and Öfversten et al (2004) analysed yield trends in long-term yield datasets for cereals but neither identified explicitly any trend due to changes in the climate. The difference between sugarbeet and wheat in response to climate changes is probably due to the different processes of yield formation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences for wheat were reported from areas differing in growing conditions from those in the Nordic areas (Calderini et al, 1995). The genetic gains in NUE for wheat and oat attributable to plant breeding reflect genetic gains in grain yields for the species (Ortiz et al, 1998; Slafer and Peltonen‐Sainio, 2001; Öfversten et al, 2004). However, Górny (2001) for barley indicated that as the N stress increased, the landraces and old cultivars became superior to modern ones in UTE.…”
Section: Discussionmentioning
confidence: 99%